Silver Stains for proteins in polyacerylamide gels: A comparison of six methods - Ochsv, Denise C.; Mcconkeyv, Edwin H.; Sammons, David W.
Six of the most recent silver staining method for detecting polypeptides on polyacrylamide gels were compared. We found the method of Sammons et al. (Electrophoresis, 1981, 2, 135-141)to be least expensive and most reproducible, For staining gels of 1.5 mm in thickness, it is also the most sensitive method. Other methods may be preferable for staining gels 0.8 mm or less in thickness.
Keywords: POLYACRYLAMIDE GELS